An integrated risk assessment model for indoor air quality impacts on museum exhibits and human health using microclimatic indices and AgNPs treatment - Alexandru Ilieș; Tudor Caciora; Gabriela Ilieș; Thowayeb H. Hassan; Zharas Berdenov; Dorina Camelia Ilieș; Ana Cornelia Pereș; Bahodirhon Safarov; Vasile Grama; Horvath Sabina; Liliana Indrie; David Mínguez-García; et al. (PLoS ONE, 2025)
The quality of indoor air in museums directly influences the conservation of exhibits made of organic materials, but also the health of visitors, employees and restorers. Thus, monitoring the microclimate and identifying non-invasive solutions to limit its impact becomes essential for the protection of movable cultural heritage. Thus, this study aims to monitor ten indicators of indoor air quality and their impact on exhibits, visitors and employees in a museum in Romania. The data obtained were analysed using specific indexes to accurately assess the indoor microclimate risk for both human health and the preservation of exhibits. The values obtained in terms of the indexes certify the stability in terms of the quality of the indoor air. Subsequently, six ethnographic fabric samples were tested to evaluate cleaning and preservation solutions based on silver nanoparticles, aiming to reduce microbial contamination and ensure sustainable protection of organic museum textiles. The results obtained indicate a moderate risk of degradation of exhibits, mainly caused by the increased relative humidity, which exceeded the limits recommended by the international standards in force. As for human health, the applied indices show that the indoor environment does not threaten human health in general, but it still records non-compliant values of the formaldehyde indicator. Also, ionic imbalance shows poor ventilation, associated with potential discomfort and negative cognitive effects. The application of silver nanoparticle treatment has proven effective in reducing microbiological contamination, providing a sustainable conservation solution, both immediately after application and after 30 days. The study highlights the importance of constant monitoring and control of environmental parameters to ensure optimal conditions for the conservation of material heritage and to prevent risks to human health in museum spaces.